Immunomodulatory-based therapy as a potential promising treatment strat- egy against severe covid-19 patients: A systematic review (2020)
The global panic of the novel coronavirus disease 2019 (COVID-19) triggered by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to an urgent requirement for effective therapy. COVID-19 infection, especially in severely ill patients, is likely to be associated with immune dysregulation, prompting the development of novel treatment approaches. Therefore, this systematic review was designed to assess the available data regarding the efficacy of the immunomodulatory drugs used to manage COVID-19. A systematic literature search was carried out up to May 27, 2020, in four databases (PubMed, Scopus, Web of Science, and Embase) and also Clinicaltrials.gov. Sixty-six publications and 111 clinical trials were recognized as eligible, reporting the efficacy of the immunomodulatory agents, including corticosteroids, hydroxychloroquine, passive and cytokine-targeted therapies, mesenchymal stem cells, and bloodpurification therapy, in COVID-19 patients. The data were found to be heterogeneous, and the clinical trials were yet to post any findings. Medicines were found to regulate the immune system by boosting the innate responses or suppressing the inflammatory reactions. Passive and cytokinetargeted therapies and mesenchymal stem cells were mostly safe and could regulate the disease much better. These studies underscored the significance of severity profiling in COVID-19 patients, along with appropriate timing, duration, and dosage of the therapies. Therefore, this review indicates that immunomodulatory therapies are potentially effective for COVID-19 and provides comprehensive information for clinicians to fight this outbreak. However, there is no consensus on the optimal therapy for COVID-19, reflecting that the immunomodulatory therapies still warrant further investigations.